Pseudo-Hermitian trimer: Asymmetric resonances and exceptional points. (22nd March 2021) - Tikeng-Manfouo, Arnaud D; Fotsa-Ngaffo, Fernande; Kofane, T C
Abstract: A pseudo-Hermitian (PH) system made up of three coupled waveguides (trimer) with an overall balanced gain and loss is investigated in a parity time (PT)-symmetric-like regime. Remarkably, the pseudo hermiticity parameter controls the asymmetric spatial field modulation between left and right propagating waves whereby, a complex coupling arises that induces an additional source of non-Hermiticity, which in the system acts as a relative gain/loss Hellmann-Feynman correction. In this situation, we show that, transmissionless backscatterings are observed for the PH-trimer in the non PT broken phase. Interestingly, the scattering properties of PH-trimer result in multiple lasing states with different mechanisms. In particular, we show that in the PT-symmetric case, the lasing modes associated to the coherent perfect-absorption (CPA), occur from the spectral singularity induced by the Hermitian chain coupling and give rise to unidirectional invisibility in the direction of incident wave. On the contrary, additional emerging lasing modes in a PH regime result from the scattering maxima resonance. We demonstrate that this specific cases suppress the CPA-laser phenomenon and rather exhibit exceptional points characterized by reflectionless but also the points of transmissionless. Numerical beam propagations realized to emphasize the results are in good agreement with the scattering investigation until gain/loss parameter is around it's value giving resonance.